"The real pandemic's been there forever": qualitative perspectives of domestic and family violence workforce in Australia during COVID-19 - Rachel Baffsky; Kristen Beek; Sarah Wayland; Janani Shanthosh; Amanda Henry; Patricia Cullen (BMC, 2022)
Abstract Background In 2020, Australia, like most countries, introduced restrictions related to the global pandemic of coronavirus disease 2019 (COVID-19). Frontline services in the domestic and family violence (DFV) sector had to adapt and innovate to continue supporting clients who were experiencing and/or at risk of DFV. There is a need to understand from the perspective of those on the frontline how DFV service responses in different contexts impacted their working conditions and subsequent wellbeing, and what they want to see continued in 'the new normal' to inform future effective practices. We address this by reporting on findings from in-depth interviews conducted with practitioners and managers from the DFV sector in Australia. Methods Between July and September 2020 semi-structured interviews were conducted with 51 DFV practitioners and managers from a range of services and specialisations across legal, housing, health and social care services. The data was analysed using iterative thematic analysis. Results The most common service adaptations reported were shifting to outreach models of care, introducing infection control procedures and adopting telehealth/digital service delivery. Adjacent to these changes, participants described how these adaptations created implementation challenges including increased workload, maintaining quality and safety, and rising costs. Impacts on practitioners were largely attributed to the shift towards remote working with a collision in their work and home life and increased risk of vicarious trauma. Despite these challenges, most expressed a sense of achievement in how their service was responding to COVID-19, with several adaptations that practitioners and managers wanted to see continued in 'the new normal', including flexible working and wellbeing initiatives. Conclusions The pandemic has amplified existing challenges for those experiencing DFV as well as those working on the frontline of DFV. Our findings point to the diversity in workforce experiences and has elucidated valuable lessons to shape future service delivery. Given the continuing impacts of the pandemic on DFV, this study provides timely insight and impetus to strengthen the implementation of remote working and telehealth/digital support across the DFV sector and to inform better supports for DFV workforce wellbeing in Australia and other contexts. Trial registration Not a clinical intervention.